Pengaruh Fraksi Etil Asetat Daun Persea americana Mill Terhadap Folikulogenesis Ovarium Ratuss norvegicus - Wati, Dwi Retno; Aryani, Hany Puspita; Rustanti, Ely (FORIKES, 2025)
Polycystic ovary syndrome is an endocrine-metabolic disorder that has serious consequences for women's health, including causing infertility. Insulin resistance is the most common metabolic disorder. Avocado leaves contain quercetin compounds that have strong bioactive elements with free radical scavenging, anti-inflammatory, anticancer, antihyperlipidemic, and antiplatelet effects, so this may increase the number of follicles in female rats with polycystic ovary syndrome models. The purpose of this study was to determine the effect of ethyl acetate fraction of Persea americana Mill leaves on increasing folliculogenesis in the experimental model Rattus norvegicus. The study used 100-200 gram Wistar strain white rats (Rattus norvegicus) divided into four groups, namely negative control, positive control (polycystic ovary syndrome), polycystic ovary syndrome given avocado leaf extract 500 mg/kgBW and 800 mg/kgBW. The polycystic ovary syndrome model was created by injecting testosterone propionate for 14 days, after which treatment was continued for 14 days. Next, an analysis of the number of follicles in the ovaries of the mice was performed. The results showed that the negative control group showed a significant decrease in the number of follicles compared to the positive control group (p < 0.05). The avocado leaf extract group showed a significant increase in the number of follicles compared to the positive control group (p < 0.05). This study concluded that avocado leaf extract increased the number of follicles in female mice with a model of polycystic ovary syndrome.Keywords: polycystic ovary syndrome; Persea americana Mill leaves; folliculogensis ABSTRAK Sindroma ovarium polikistik adalah gangguan endokrin-metabolik yang memberi konsekuensi berat untuk kesehatan wanita, termasuk paling banyak menyebabkan infertilitas. Resistensi insulin merupakan kelainan metabolik yang paling umum. Daun alpukat mengandung senyawa kuersetin yang mempunyai unsur bioaktif kuat dengan efek radikal bebas, antiinflamasi, antikanker, antihiperlipidemia, dan antiplatelet, sehingga hal ini memungkinkan dapat meningkatkan jumlah folikel pada tikus betina model sindroma ovarium polikistik. Tujuan penelitan ini adalah mengetahui pengaruh fraksi etil asetat daun Persea americana Mill yang dapat meningkatkan folikulogenesis pada Rattus norvegicus model eksperimental. Penelitian menggunakan tikus putih strain Wistar (Rattus norvegicus) 100-200 gram yang dibagi menjadi empat kelompok, yaitu kontrol negatif, kontrol positif (sindroma ovarium polikistik), sindroma ovarium polikistik diberi ekstrak daun daun alpukat 500 mg/kgBB dan 800 mg/kgBB. Model sindroma ovarium polikistik dibuat dengan menginjeksi testoteron propionate selama 14 hari, setelah itu dilanjutkan pengobatan selama 14 hari. Selanjutnya dilakukan analisis jumlah folikel pada ovarium tikus. Hasil penelitian menunjukkan bahwa kelompok kontrol negatif menunjukkan penurunaan jumlah folikel secara signifikan dibandingkan dengan kelompok kontrol positif (p <0,05). Kelompok ekstrak daun alpukat menunjukkan peningkatan signifikan jumlah folikel dibandingkan dengan kelompok kontrol positif (p <0,05). Penelitian ini menyimpulkan bahwa ekstrak daun alpukat meningkatkan jumlah folikel pada tikus betina model sindroma ovarium polikistik.Kata kunci: sindroma ovarium polikistik; daun Persea americana Mill; folikulogensis